Histopathological Changes in the Livers of Broiler Chicken Supplemented with Turmeric (Curcuma longa) - AL-Sultan, S.I.; Gameel, A.A. (International Journal of Poultry Science, 2004)
Four groups of broiler chicken (A, B, C and D) of 50 birds each , received dietary supplement of turmeric (Curcuma longa) at concentrations of 0.0, 2.5, 5.0 and 10% respectively. Liver sections from birds of all groups showed parenchymal and portal infiltration of mononuclear cells and hyperaemia of portal vessels. Dilatation of bile ducts, mild proliferation of biliary epithelium and periportal hepatocyte degeneration was noticed only in groups B, C and D particularly group B birds killed three weeks after treatment. These changes were related to feeding of Turmeric (Curcuma longa).